Adding biotic complexity alters the metabolic benefits of mutualism. (1st August 2016) - Harcombe, William R.; Betts, Alex; Shapiro, Jason W.; Marx, Christopher J.
Abstract: Mutualism is ubiquitous in nature and plays an integral role in most communities. To predict the eco‐evolutionary dynamics of mutualism it is critical to extend classic pair‐wise analysis to include additional species. We investigated the effect of adding a third species to a pair‐wise mutualism in a spatially structured environment. We tested the hypotheses that selection for costly excretions in a focal population (i) decreases when an exploiter is added (ii) increases when a third mutualist is added relative to the pair‐wise scenario. We assayed the selection acting on Salmonella enterica when it exchanges methionine for carbon in an obligate mutualism with an auxotrophic Escherichia coli . A third bacterium, Methylobacterium extorquens, was then added and acted either as an exploiter of the carbon or third obligate mutualist depending on the nitrogen source. In the tripartite mutualism M. extorquens provided nitrogen to the other species. Contrary to our expectations, adding an exploiter increased selection for methionine excretion in S. enterica . Conversely, selection for cooperation was lower in the tripartite mutualism relative to the pair‐wise system. Genome‐scale metabolic models helped identify the mechanisms underlying these changes in selection. Our results highlight the utility of connecting metabolic mechanisms and eco‐evolutionary dynamics.